Breastfeeding Among Women With Physical Disabilities in the United States. (May 2018) - Powell, Robyn M.; Mitra, Monika; Smeltzer, Suzanne C.; Long-Bellil, Linda M.; Smith, Lauren D.; Rosenthal, Eliana; Iezzoni, Lisa I.
Background: The benefits of breastfeeding are well established, and breastfeeding is now widely practiced in the United States. Although increasing numbers of women with physical disabilities are having children, little information is available about breastfeeding practices among these women. Nonetheless, the children of women with physical disabilities should benefit from breastfeeding just as children of nondisabled mothers do. Research aim: This study aimed to explore the facilitators and barriers to breastfeeding among women with physical disabilities. Methods: This study involved semistructured telephone interviews with a convenience sample of women ( N = 25) with diverse physical disabilities from across the United States. All participants had given birth within the past 10 years. Interviews were audio-recorded, professionally transcribed, and analyzed using content analysis. Results: Analyses found four broad themes indicating facilitators to breastfeeding: (a) adaptations and equipment, (b) use of breast pump, (c) physical assistance from others, and (d) peer support. We also found five broad themes suggesting barriers to breastfeeding: (a) lack of supports, (b) disability-related health considerations, (c) limited information, (d) difficulties with milk production, and (e) difficulties latching. Conclusion: The need for greater supports for women with physical disabilities who desire to breastfeed as well as information for women and their clinicians about facilitating breastfeeding.